Sustainable Strategy to Reduce Winter Energy Consumption: Incorporating PCM Aggregates and Rice Husk Ash–Fly Ash Matrix into Concrete - Mingming Zhang; Shan Gao; Jin Xu; Lidong Wang; Mengyan Xu; Honghao Ying (Buildings)
This study improved the thermal damping of concrete with rice husk ash (RHA)–fly ash (FA) matrix and three phase-change material (PCM) aggregates with phase change temperatures between −15 and 5 °C, which are expected to reduce winter energy consumption in cold regions when used as building envelope structures. Firstly, the strength of concrete was studied. Secondly, the dynamic and transient thermal response of concrete was evaluated through thermal conductivity and thermal diffusivity. Based on nuclear magnetic resonance experiments, the changes in the pore volume and fractal dimension of RHA–FA matrix and PCM aggregate added to concrete were studied. Through correlation analysis, a macroscopic performance prediction model based on pore characteristics was obtained. The results indicated that the incorporation of PCM aggregate reduced concrete strength, while an appropriate RHA–FA matrix contributed to enhancing concrete strength. Both the PCM aggregate and RHA–FA matrix were beneficial for improving the thermal damping properties of concrete. For 15% RHA–30% FA 100% PCM concrete, the thermal conductivity can be reduced by 53%, the thermal diffusivity can be reduced by 64%, the limiting temperature decreased by 5.5 °C, and the thermal damping coefficient increased by 48%. The nuclear magnetic resonance test results showed that PCM aggregate increased the pore volume and decreased the fractal dimension, while an appropriate RHA–FA matrix helped to reduce the pore volume. The macroscopic properties of RHA–FA–PCM aggregate concrete were highly correlated with the capillary pore volume and fractal dimension. A two-parameter prediction model based on pore characteristics can effectively predict the macroscopic properties of concrete.